57.7k views
3 votes
Please help!

(Vieta's Formulas) Let
r,
s, and
t be solutions to the equation
$2x^3 - 3x^2 + 4x - 1 = 0$. Find
$r^2+s^2+t^2$.


Please include an explanation as well :)

1 Answer

0 votes

We are given the polynomial:

2x³ - 3x² + 4x - 1 = 0

We need to find the value of r² + s² + t² where r,s,t are the solutions.

Simplifying r² + s² + t²:

r² + s² + t² = (r + s + t)² - 2(rs + st + rt)

[since a²+b²+c² = (a+b+c)² - 2(ab + bc + ca)]

Using the Vieta's formulae:

Above, we can see that in order to find the value of r² + s² + t², we need to find the value of the sum of solutions and sum of solutions taken 2 at a time.

Sum of roots:

We know that the Vieta's formula to find the sum of roots is:

Sum of roots =
-(b)/(a)

Where b and a are the coefficients from the general form: ax³ + bx² + cx - d

We notice that for the given equation, b = -3 ; a = 2

Sum of roots =
-((-3)/(2))

Sum of roots =
(3)/(2)

Hence, the sum of roots (r + s + t) = 3/2

Sum of roots taken two at a time:

We know that the Vieta's formula to find the sum of roots taken 2 at a time is: Sum of roots taken 2 at a time =
(c)/(a)

Where c and a are the coefficients from the general form: ax³ + bx² + cx - d

for the given equation, c = 4 ; a = 2

Sum of roots taken 2 at a time =
(4)/(2)

Sum of roots taken 2 at a time = 2

Hence, the sum of roots taken 2 at a time (rs + st + rt) = 2

Finding the value of r² + s² + t²:

We proved before that:

r² + s² + t² = (r + s + t)² - 2(rs + st + rt)

now that we know the values of (r + s + t) and (rs + st + rt), we can plug those values to get our answer

r² + s² + t² = (
(3)/(2))² - 2(2)

r² + s² + t² = (
(9)/(4\\)) - 4

r² + s² + t² =
(9 - 16)/(4\\)

r² + s² + t² =
(-7)/(4) = -1.75

Hence, the value of r² + s² + t² is -1.75

User Vikas Madhusudana
by
4.9k points